1982
DOI: 10.4049/jimmunol.128.6.2453
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of human B lymphocyte function by cyclophosphamide.

Abstract: The immune responses of 16 patients with nonneoplastic immune mediated diseases including Wegener's granulomatosis, systemic necrotizing vasculitis, cutaneous vasculitis, and relapsing nodular panniculitis were evaluated before and during therapy with chronic low-dose (2 mg/kg/day) cyclophosphamide. A striking selective suppression of B cell function was noted as measured by PWM-induced immunoglobulin secretion. This suppression was a direct effect on the B cells themselves because T cell function, measured by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

1987
1987
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…This alkylating agent remains the most effective drug for the control of disease activity. It targets all types of proliferating immune cells nonspecifically, influencing cell-mediated and humoral immune response [6]. It has most profound effect on B cells function and stronger suppressive effect on CD8+ T cells than CD4+ T lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This alkylating agent remains the most effective drug for the control of disease activity. It targets all types of proliferating immune cells nonspecifically, influencing cell-mediated and humoral immune response [6]. It has most profound effect on B cells function and stronger suppressive effect on CD8+ T cells than CD4+ T lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Cambridge et al suggested that total immunoglobulins are produced by long-lived plasma cells, which do not express the CD20 antigen and are not affected by anti-CD20 monoclonal antibody [21]. Several groups of investigators suggest that the pathogenic role of Blymphocytes in Wegener's granulomatosis goes beyond their function for autoantibody production [6,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[35][36][37][38][39] En este contexto, se consideró hipotéticamente que los clones linfocitarios potencialmente autoreactivos, capaces de generar una respuesta de Acs contra EGF autólogo, reemergen de la depleción máxima de linfocitos inducida por la quimioterapia (nadir de linfopenia), ampli¿ cados con ventaja homeostática. [40,41] Sobre la base de estos conceptos y los resultados de las investigaciones preclínicas, se propuso un esquema terapéutico combinando vacuna, quimioterapia y más vacuna (VQV). Este Original Scienti¿ c Articles esquema se evaluó en el quinto ensayo clínico fase I/II (Piloto 5), comenzado en 2001 en el Hospital Hermanos Ameijeiras (HHA) de la Habana, utilizándose la formulación CIMAvax EGF (EGF/ P64k/Montanide ISA 51) en 20 pacientes con CPCNP estadios IIIB/IV.…”
Section: Original Scienti¿ C Articlesunclassified
“…CYC depletes certain populations of T cells 22 and suppresses B cells. 23 Additionally, CYC is immunosuppressive by virtue of toxicity to lymphocytes, with less impact on haematopoietic stem cells (HSCs). In contrast, myeloablative autologous HSCT treatment depletes both lymphocytes and HSCs by total body irradiation, with reconstitution of these population through CD34-selected HSC autograft.…”
Section: Introductionmentioning
confidence: 99%